PROFILE OF TENUN SONGKET UNGGAN CRAFTING INDUSTRY AT KENAGARIAN UNGGAN KECAMATAN SUMPUR KABUPATEN SIJUNJUNG - Novrizal, Ari; Erita, Yeni; Prari Keslan, Widya (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The purpose of this research is to know Profile of Tenun Songket Unggan at Kenagarian Unggan Kecamatan Sumpur Kudus Kabupaten Sijunjung.Type of this research is descriptive. Population of this research is all of Tenun Songket Unggan worker at Kecamatan Sumpur Kudus that are include of 4 groups. Sample of respondent is taken using Proporsional Random Sampling with 60% proporsional where amount of sample is 98 people. Technique of analysis data uses analysis with percentage formula. Meanwhile, technique of data collection is toward questionnaires or instruments.The result of research is determined that are 1) Average capital of every industry Tenun Songket Uggan which comes from BANK loan by using mean to average is Rp.Â 8.000.000 - Rp. 9.500.000 (55.10%) and fluent capital Rp. 100.000 â Rp. 200.000 (57.14%) every groups. Furthermore, difficulty of cultivation capital Tenun Songket Unggan industry is profit Bank range which is high (75.51%). 2) Main raw material Tenun Songket Unggan industry is Injek Yarn (100%), and supported yarn is Tembago Yarn and Gold Yarn. For available raw material (54.08%) enough available, and this raw material is get from neighbor village (79.59%) with directly selling to market (79.59%). 3) This worker of Tenun Songket Unggan industry group is average steady worker (82.65%) with activity job between 5 until 7 of hours every day (61.22%). Meanwhile, high skill of worker is sewing skill (51.02%) and there are problems Tenun Songket Unggan crafting program, but it is not difficult. 4) Marketing where is way of marketing the result of Tenun Songket Unggan that directly sell in industry location (77.55%), and main village of seller is Sijunjung village (100%), on the other word of Sijunjung (64.29%) that is foreign country. Fluent of marketing is (55.10%) and constraint in marketing is about narrow as marketing region (78.57%). There resolve this problem that promote of industry (79.59%).Â Â